The Return to Labor Market Mobility: An Evaluation of Relocation Assistance for the Unemployed - Marco Caliendo; Steffen Künn; Robert Mahlstedt (Institute for the Study of Labor (IZA), 2015)
In many European countries, labor markets are characterized by high regional disparities in terms of unemployment rates on the one hand and low geographical mobility among the unemployed on the other hand. This is somewhat surprising and raises the question of why only minor shares of unemployed job seekers relocate in order to find employment. The German active labor market policy offers a subsidy covering moving costs to incentivize unemployed job seekers to search/accept jobs in distant regions. Based on administrative data, this study provides the first empirical evidence on the impact of this subsidy on participants' prospective labor market outcomes. We use an instrumental variable approach to take endogenous selection based on observed and unobserved characteristics into account when estimating causal treatment effects. We find that unemployed job seekers who participate in the subsidy program and move to a distant region receive higher wages and find more stable jobs compared to non-participants. We show that the positive effects are (to a large extent) the consequence of a better job match due to the increased search radius of participants.
Keywords: J61; J64; J68; D04; C26; 330; evaluation; active labor market policy; labor market mobility; Instrumental variable approach